Interpretation of Gender Bias in QS. Al-Taubah/9 verse 71: Critical Review of Tafsir Al-Qur’an Tematik The Ministry of Religion Affairs Republic of Indonesia - Ainurrofiq, Faiq; Amir, Abdul Muiz; Sempo, Muhammad Widus (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2020)
This paper aims to explore critically the interpretation result of QS. Al-Taubah/9:71 in Tafsir Qur‟anTematik by the Ministry of Religion Affairs Republic of Indonesia. This is conducted because it issuspected that it contains a gender bias interpretation. This research used a critical qualitative-interpretativedesign by investigating the interpretation of QS. al-Taubah / 9: 71 using a contextualizationinterpretation. The findings reveal that the Thematic Interpretation of Al-Quran by the Ministry ofReligion affairs published for the first time in 2009 represents the interpretation of the QS. al-Taubah/9:71 as legitimacy of limiting the area of political leadership for women. Therefore, the product of suchinterpretations tends to be biased because it limits the area of state leadership based on a particular gender.This interpretation seems to contrast with the meaning of the verse that is found through the exploration oftextual, contextual-historical, and dynamic contextual approaches. The meaning obtained from this versediscusses about the socio-spiritual relationship in the internal Muslim community only, rather than thepolitical context. The same results can also be seen in Tafsir al-Wajiz, in which the work is also theinterpretation of the Ministry of Religion published in 2016, as well as the interpretation of scholars invarious classical commentaries. The implication of the results of the interpretation of gender bias in TafsirQur‟an Tematik can have an impact on government policies in positioning the women in the society,especially in the area of structural leadership of country. This research contributes to the study of Qur’anicexegesis and gender discourse in Islam by offering a critical framework for evaluating genderedinterpretations of religious texts. Additionally, it demonstrates the importance of contextual hermeneutics inaddressing structural biases in Islamic exegesis and proposes a more inclusive approach to Qur’anicinterpretation.